2021
DOI: 10.1111/add.15746
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal smoking, alcohol and caffeine exposure and maternal‐reported attention deficit hyperactivity disorder symptoms in childhood: triangulation of evidence using negative control and polygenic risk score analyses

Abstract: Background and aims: Studies have indicated that maternal prenatal substance use may be associated with offspring attention deficit hyperactivity disorder (ADHD) via intrauterine effects. We measured associations between prenatal smoking, alcohol and caffeine consumption with childhood ADHD symptoms accounting for shared familial factors.Design: First, we used a negative control design comparing maternal and paternal substance use. Three models were used for negative control analyses: unadjusted (without confo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 70 publications
6
13
0
1
Order By: Relevance
“…The phenome-wide association study (PheWAS) provided insight into potentially complex mechanisms of genetic liability to environmental pathways of risk. In addition to indices of socioeconomic status (SES), the addiction-rf was correlated with maternal tobacco smoking during pregnancy and with attention deficit hyperactivity disorder, in line with evidence that effects ascribed to the prenatal environment may also be mediated by the inheritance of risk loci 43,44 . The addiction-rf PRS was associated with a family history of serious mental illness, which likely represents an amalgam of genetic and environmental vulnerability 45 .…”
Section: Articlesupporting
confidence: 61%
“…The phenome-wide association study (PheWAS) provided insight into potentially complex mechanisms of genetic liability to environmental pathways of risk. In addition to indices of socioeconomic status (SES), the addiction-rf was correlated with maternal tobacco smoking during pregnancy and with attention deficit hyperactivity disorder, in line with evidence that effects ascribed to the prenatal environment may also be mediated by the inheritance of risk loci 43,44 . The addiction-rf PRS was associated with a family history of serious mental illness, which likely represents an amalgam of genetic and environmental vulnerability 45 .…”
Section: Articlesupporting
confidence: 61%
“…In contrast, it is crucial to note that for many ADHD risk factors, the association appears not to be causal but explained by genetic or familial confounds, or else is reverse causality due to evocative genotype‐environment correlation. For example, a causal role has not been supported for maternal smoking (Haan et al., 2022; Rice et al., 2018) and maternal pregnancy weight gain (Musser et al., 2017). Child maltreatment had only a small causal association with ADHD symptoms in a population study that controlled for familial and genetic confounding (Dinkler et al., 2017) More studies of these kinds are needed to determine which risk factors mandate intervention.…”
Section: Environmentsmentioning
confidence: 99%
“…Observed associations may reflect confounding by unknown or unmeasured shared familial factors that influence maternal exposure and offspring neurodevelopmental outcomes . Genetic confounding, when the same genetic factors are independently associated with both the exposure and outcome, has consistently been shown to explain the association between smoking during pregnancy and risk for ADHD in children using different causally informative designs . Determining if exposure to prenatal factors is causal is important because misleading evidence about the causes of neurodevelopmental conditions can result in unnecessary worry for pregnant individuals and hinder attention to more appropriate intervention targets.…”
Section: Introductionmentioning
confidence: 99%
“…However, different magnitudes of association between maternal vs paternal PGS with exposures would suggest that the use of paternal exposures as a negative control may not be appropriate. For example, some negative control studies have found stronger associations between prenatal substance use (smoking, alcohol, and caffeine) and offspring ADHD for mothers compared with fathers, 15,22 despite broader triangulation of evidence suggesting no causal effects. 12,13,15 During pregnancy, the substance use of the pregnant individual is a more severe phenotype than that of their nonpregnant partner, owing to the strong pressure on pregnant individuals to quit.…”
mentioning
confidence: 99%
See 1 more Smart Citation